Investigating the cell biology of plant infection by the rice blast fungus Magnaporthe oryzae. (December 2016) - Yan, Xia; Talbot, Nicholas J
Highlights: Hydrophobins play key roles in mediating appressorium development in rice blast disease. Ras GTPase signalling acts upstream of cAMP and MAP kinase pathways for appressorium development. Fungal effectors act to suppress plant immunity and may have numerous separate specificities. Perception of the pathogen can involve integrated decoy domains in rice immune receptors. M. oryzae can modulate plant hormone signaling to suppress immunity. Abstract : Rice blast disease is a major constraint on worldwide rice production and understanding the biology of plant infection is a priority for development of new disease control strategies. Recent advances in live cell imaging, coupled with tractability of both host and pathogen to molecular genetics and genomics, has made the rice blast pathosystem an important model for understanding plant disease. Here we review recent advances in understanding the cell biology of plant infection and, in particular, the remarkable ability of the rice blast fungus to invade plant tissue and manipulate the host plant using a battery of secreted effector proteins. These fungal effectors suppress plant immunity, alter cellular organisation, and facilitate rapid fungal growth.